Exploring prehabilitation interventions for patients with gynaecological cancer undergoing radiotherapy: A scoping review - McGladrigan, Elizabeth; Wrench, Elizabeth; Dean, Ewan; O’Neil, Aneurin; Ashmore, Lisa; Gaffney, Christopher (PLOS ONE, 2025)
Purpose Radiotherapy imposes a significant physiological and psychological burden on gynaecological cancer patients. Prehabilitation is being increasingly used to prepare individuals for cancer treatment and improve their well-being and resilience. Whilst prehabilitation has demonstrated benefit for individuals undergoing cancer surgery, the structure, role and implementation of prehabilitation prior to radiotherapy are poorly defined and relatively unexplored. This scoping review aims to provide a comprehensive overview of the current literature regarding prehabilitation interventions for individuals with gynaecological cancer undergoing radiotherapy. Methods This review was conducted following the gold-standard Joanna Briggs Institute guidelines for scoping reviews. Literature searches were completed in October 2024 across: the Allied and Complementary Medicine Database; British Nursing Index; Cumulative Index to Nursing and Allied Health Literature; Cochrane library (Controlled trials and systematic reviews); Embase; Medical Literature Analysis and Retrieval System Online; and the Psychological Information Database. Grey literature searches were conducted via Google Scholar, Overton.io, and Trip Pro Medical Database. Results Ninety records met the inclusion criteria, pertaining to 56 studies. Cervical cancer was the most represented gynaecological cancer type across studies. A small number of multimodal prehabilitation studies were identified (n = 4). Studies evaluating unimodal interventions were more common, with nutritional interventions (n = 24) being the most frequent, followed by psychological (n = 22) and physical exercise (n = 6) interventions. There was considerable variation across studies in respect to intervention initiation, duration, delivery and outcome measures. Conclusions The physiological and psychological impacts of cancer diagnosis and treatment are closely entwined. Further development of multimodal prehabilitation to cohesively address these is an important area for future research. Studies evaluating exercise interventions are relatively unexplored in this patient population and the potential barriers to engagement must be considered. Future research should focus on complete and transparent reporting of interventions, with input from those with lived experience, and adopting a standardised set of outcome measures reported across all trials.